Knowledge gaps that hamper prevention and control of Mycobacterium avium subspecies paratuberculosis infection. (22nd September 2017) - Barkema, H. W.; Orsel, K.; Nielsen, S. S.; Koets, A. P.; Rutten, V. P. M. G.; Bannantine, J. P.; Keefe, G. P.; Kelton, D. F.; Wells, S. J.; Whittington, R. J.; Mackintosh, C. G.; Manning, E. J.; et al.
Summary: In the last decades, many regional and country‐wide control programmes for Johne's disease (JD) were developed due to associated economic losses, or because of a possible association with Crohn's disease. These control programmes were often not successful, partly because management protocols were not followed, including the introduction of infected replacement cattle, because tests to identify infected animals were unreliable, and uptake by farmers was not high enough because of a perceived low return on investment. In the absence of a cure or effective commercial vaccines, control of JD is currently primarily based on herd management strategies to avoid infection of cattle and restrict within‐farm and farm‐to‐farm transmission. Although JD control programmes have been implemented in most developed countries, lessons learned from JD prevention and control programmes are underreported. Also, JD control programmes are typically evaluated in a limited number of herds and the duration of the study is less than 5 year, making it difficult to adequately assess the efficacy of control programmes. In this manuscript, we identify the most important gaps in knowledge hampering JD prevention and control programmes, including vaccination and diagnostics. Secondly, we discuss directions that research should take to address those knowledge gaps.